Effect of Organosilicone Surfactant on Uptake and Translocation of Glyphosate in Pennisetum Polystachion L - Teo, Kee Chiong (1997)
The effect of adding organosilicone surfactant, Pulse® on efficacy, uptake and translocation of glyphosate (Roundup®) for the control of Pennisetum polystachion was evaluated in the glasshouse. The dose-response study with glyphosate on 9-week old P. polystachion showed that at the rate of 1.08 kg a.e.iha, glyphosate caused complete mortality of the plants. It was estimated that dosage between 360 to 540 g a.e./ha gave 50% mortality. When Pulse® was added to the glyphosate spray solutions, the bioefficacy of glyphosate on P. polystachion increased as the concentration of Pulse® increased. The optimum concentration ofPulse® was 0.2 % w/w above which no significant increase in the bioefficacy was observed. Spray deposition studies using tlourescent tracer technique revealed that the mixture of glyphosate and Pulse® gave 42% higher spray deposition compared to glyphosate alone, thus contributing to the increase in bioefficacy of glyphosate observed in the mixture.